Teacher's Strategy for Increasing Students' Creative Thinking Ability Through Open-Ended Learning in Elementary Schools - Baharuddin Baharuddin; Andi Agustang (JED (Jurnal Etika Demokrasi), 2022)
This research is based on students’ creative thinking abilities, which can be influenced by two factors, namely internal factors, and external factors. As an external factor, the teacher is a facilitator in applying the right approach to the learning process. The learning approach applied by the teacher will have an impact on students’ creative thinking abilities. This study aims at discovering (1) the description of the implementation of open-ended learning as a strategy to improve students’ creative thinking ability at SDN Mangkura V Makassar, (2) the description of students’ creative thinking ability before and after implementing open-ended learning approach at SDN Mangkura V Makassar, (3) the influence of the implementation of open-ended learning approach on students’ creative thinking ability at SDN Mangkuira V Makassar. The type of research employed in this study is a quasi-experimental design with pretest-posttest nonequivalent control group design. Data were collected through observation, tests, and documentation. The research populations were all students of grade IV at SDN Mangkura V Makassar, with a total of 63 students. The sampling technique used in this study was non-probability sampling; thus, it obtained 54 students. Data were analysed by employing descriptive analysis and inferential analysis. The study results reveal that the mean score before the implementation of the open-ended learning approach is 29.26, which is in a low category. After the implementation of the open-ended learning, approach is 45.70, which is in the high category. It can be concluded that students’ creative thinking skills increase through open-ended learning because, with open-ended learning, they have the freedom to express creative ideas in problem-solving.Penelitian ini berlandaskan pada kemampuan berpikir kreatif siswa dapat dipengaruhi oleh dua faktor, yaitu faktor internal dan faktor eksternal. Guru sebagai faktor eksternal merupakan fasilitator dalam penerapan pendekatan yang tepat pada proses pembelajaran. Pendekatan pembelajaran yang diterapkan guru akan berdampak pada kemampuan berpikir kreatif siswa. Penelitian ini bertujuan untuk mengetahui (1) gambaran pelaksanaan pembelajaran open-ended sebagai strategi meningkatkan kemampuan berpikir kreatif peserta didik di SD Negeri Mangkura V kota Makassar, (2) gambaran kemampuan berpikir kreatif siswa sebelum dan sesudah pelaksanaan pembelajaran open-ended di SD Negeri Mangkura V Makassar, (3) pengaruh pelaksanaan pembelajaran open-ended terhadap peningkatan kemampuan berpikir kreatif peserta didik SD Negeri Mangkura V Makassar. Jenis penelitian  yang digunakan dalam penelitian ini adalah Quasi Experimental Design dengan desain Pretest-posttest nonequivalent control group design. Teknik pengumpulan data melalui observasi, tes, dan dokumentasi. Populasinya adalah seluruh siswa kelas IV SD Negeri Mangkura V Makassar sebanyak  63 orang siswa. Teknik penyampelan yang digunakan adalah non probability sampling sehingga diperoleh sampel sebanyak 54 orang siswa. Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis inferensial. Hasil penelitian menunjukkan bahwa rata-rata (mean) skor sebelum pelaksanaan pembelajaran open-ended adalah 29,26 dengan kategori rendah dan sesudah pelaksanaan pembelajaran open-ended adalah 45,70 dengan kategori tinggi. Dapat disimpulkan bahwa kemampuan berpikir kreatif meningkat melalui pembelajaran open-ended karena dengan pembelajaran open-ended, peserta didik memiliki kebebasan berkreasi menuangkan gagasan kreatif dalam pemecahan masalah.